2014
DOI: 10.7314/apjcp.2014.15.16.6843
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Metastasis of Lung Cancer Demonstrate Decreased Diffusion on Diffusion-Weighted Magnetic Resonance Imaging

Abstract: Background: Diffusion-weighted magnetic resonance imaging (DWI) is reported to be useful for detecting malignant lesions. The purpose of this study is to clarify characteristics of imaging, detection rate and sensitivity of DWI for recurrence or metastasis of lung cancer. Methods: A total of 36 lung cancer patients with recurrence or metastasis were enrolled in this study. While 16 patients underwent magnetic resonance imaging (MRI), computed tomography (CT) and positron emission tomography-computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… Yuan et al (2022) compared the tissue microbiological co-occurrence networks in 134 lung cancer patients without recurrence or metastasis (non-RM) and 174 patients with recurrence or metastasis (RM) and found that the co-occurrence network of non-RM was more complicated than RM. Recurrence and metastasis as well as survival in our study are both important prognostic indicators of cancer patients ( Usuda et al, 2014 ). Our study shows that the poorer survival of CRC patients is accompanied by a microbiome co-occurrence network of reduced complexity in tissues.…”
Section: Resultsmentioning
confidence: 60%
“… Yuan et al (2022) compared the tissue microbiological co-occurrence networks in 134 lung cancer patients without recurrence or metastasis (non-RM) and 174 patients with recurrence or metastasis (RM) and found that the co-occurrence network of non-RM was more complicated than RM. Recurrence and metastasis as well as survival in our study are both important prognostic indicators of cancer patients ( Usuda et al, 2014 ). Our study shows that the poorer survival of CRC patients is accompanied by a microbiome co-occurrence network of reduced complexity in tissues.…”
Section: Resultsmentioning
confidence: 60%
“…The reasons for this result were speculated as follows: first, lesions with a poorer prognosis tend to be more malignant and more compact than those with a better prognosis and therefore have more restricted diffusion of water molecules within them, resulting in a lower diffusion-related parameter. 28 Second, compared to ADC stand and D, which only reflect diffusion information in a specific direction, DDC represents the average diffusion information in all directions and is therefore more sensitive to changes in diffusion information. 21,22 D* is one of the perfusion-related parameters of biexponential IVIM, the size of which was mainly proportional to the average intramicrovascular blood velocity.…”
Section: Discussionmentioning
confidence: 99%
“…This study further explored the value of the diffusion‐related parameter DDC of the stretched‐exponential model IVIM in the assessment of PFS in NSCLC and found a trend toward a lower risk as the DDC value increased, which to some extent suggests that in the assessment of prognosis of NSCLC patients using diffusion‐related parameters, the stretched‐exponential model may be more advantageous than monoexponential and biexponential models. The reasons for this result were speculated as follows: first, lesions with a poorer prognosis tend to be more malignant and more compact than those with a better prognosis and therefore have more restricted diffusion of water molecules within them, resulting in a lower diffusion‐related parameter 28 . Second, compared to ADC stand and D , which only reflect diffusion information in a specific direction, DDC represents the average diffusion information in all directions and is therefore more sensitive to changes in diffusion information 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…Several investigation regarding the ADC measurement with DWI have been widely performed, and taking the Asian Pacific Journal of Cancer Prevention for example, published articles mainly concentrated on the diagnosis and differential diagnosis of human tumors. For instance, evidence indicated that DWI might be useful for detection of recurrence and metastasis of lung cancer, or ADC measurements may be utilized to improve the differential diagnosis accuracy of benign and malignant focal liver lesions, DWI has higher potential than other imaging methods like positron emission tomography in assessing pulmonary nodules and masses, yet no more other publishes focused on the differential diagnosis of BC which may restrict a wide references and applications of DWI in the differential diagnosis of human tumors (Han et al, 2014;Usuda et al, 2014a;2014b). The most important conclusion of the current study is that the ADC values of lymph nodes with metastasis was apparently lower compared to those of benign or normal lymph nodes, indicating that DWI might be an useful method in the characterization and diagnosis of malignant LNM in BC patients by means of measuring the ADC values.…”
Section: Discussionmentioning
confidence: 99%